A self-crosslinking, double-functional group modified bacterial cellulose gel used for antibacterial and healing of infected wound - Xie, Yajie; Qiao, Kun; Yue, Lina; Tang, Tao; Zheng, Yudong; Zhu, Shihui; Yang, Huiyi; Fang, Ziyuan (Bioactive materials, 2022)
Cellulose/chitosan composite, as a mature commercial antibacterial dressing, is an important type of wound repair material. However, how to achieve the perfect compound of two components and improve antibacterial activity is a major, lingering issue. In this study, a bifunctional group modified bacterial cellulose (DCBC) was prepared by carboxymethylation and selective oxidation. Further, the chitosan (CS) was compounded in the network of DCBC by self-crosslinking to form dialdehyde carboxymethyl bacterial cellulose/chitosan composites (S-DCBC/CS). The aldehyde group can react with amino of CS by Schiff base reaction. The carboxyl group of DCBC and the amorphous distribution of CS molecular chains increase the antimicrobial properties of composites. The bacteriostatic rate of composites could be higher than 95%. Bacteria can be attracted onto the surface of composites, what we call it “directional adhesion antibacterial effects”. In particular, a kind of large animal wound model, deep Ⅱ degree infected scald of Bama miniature pig, was used to research the antimicrobial and healing properties of materials. The S-DCBC/CS can effectively inhibit bacterial proliferation of wound and kill the bacteria. The wound healing rate of S-DCBC/CS was up to 80% after three weeks. The composites show better antibacterial and promoting concrescence effects than traditional chitosan dressings. [Display omitted] •A network composites from dialdehyde carboxylmethyl BC with chitosan that has good antibacterial properties.•Deep Ⅱ degree infected scald of Bama pig was used to research the antimicrobial and healing properties of S-DCBC/CS.•The S-DCBC/CS composites could promote epidermal growth and collagen production.